ORGANIZATIONAL STRUCTURES IN MANAGEMENT OF RESEARCH DEVELOPMENTS IN LABOR-INTENSIVE BRANCHES OF INDUSTRY IN UZBEKISTAN - 1.AbdurahmanovaMunovar; 2.DalievKhusan (The journal of contemporary issues in business and government, 2021)
At the present stage of strategic development of the Republic of Uzbekistan, the integration issues of education, science and production are acquiring more and more practical significance. Science and technology, constituting an element of the productive forces of society, are one of the basic conditions of social progress, and science becomes in full measure a direct productive force. In this paper, we aim to investigate the effects of organizational structures and learning organization on the integration of education, science and industry contributes to the formation of new social relations. Furthermore, we explore advances in science and technology in a number of industries and methods to characterize the nature of workers’ labor.